Gender and Native-ness Differences in the Use of Speech Fillers in Political Interviews - AL-Faragy, Rola Fawwaz Hamad; Mohammed, Fuad Jassim (Al-Adab Journal, 2022)
This research aims to find out types and functions of speech fillers used by politician interviewees. It also investigates gender and native-ness differences in the use of SFS among participants. The data of this study come from eight extracted episodes taken from the corpus of conflict zone (CZ) talk show. The data have been analyzed and classified based on the theories proposed by Stenstrom (1994) and Rose (1998). A qualitative analysis has been followed in dealing with functions of SFs. A quantitative analysis is also applied in the course of counting frequencies and percentages of SFs. The results show that time is required for planning, especially when difficult topics are discussed. Results show that all participants used all types of SFs with unlexicalized SFs being used more frequently. In terms of functions of SFs, Female participants used all functions of SFs based on the theory of Stenstrom. They are breathing, filling pause, hesitation mark, starter, shift marker, empathizing, mitigating, editing term, time creating device, holding the turn and sequencer, while the male groups used all functions except shift marker. Breathing is the dominating function of SFs used by all participants with vast distinction with other functions. In contrast, shift marker has the least used function.